Dynamic caustics in unidirectional fiber-reinforced composites with mode I cracks: Experiment and numerical simulation. Issue 4 (12th March 2018) - Hao, Wenfeng; Sheng, Xixuan; Guo, Guangping; Chen, Xinwen; Zhu, Jianguo
ABSTRACT: The stress singularities of a dynamic crack tip in orthotropic composites were studied through caustics. The parametric equations of the caustic and its initial curve surrounding the dynamic crack tip were derived through the elastic dynamic crack solutions of orthotropic composites and the basic principle of reflective caustics. Theoretical caustics and initial curves for three kinds of orthotropic composites were simulated, and the effects of crack velocity on the caustics and initial curves were analyzed. In comparison with numerical results, the dynamic caustic experiment was performed for dynamic cracks along the material axes in unidirectional, fiber-reinforced composites under drop-hammer, three-point-bend loading.